Beda Pengaruh Antara Microwave Diathermy, Transverse Friction dan Mills Manipulasi dengan Microwave Diathermy dan Transverse Friction Terhadap Penurunan Nyeri Akibat Tennis Elbow Tipe II (Lembaga Penerbitan Universitas Esa Unggul, 2007)
Objectives: The purpose of this study was to compare the intervention of MWD, trans-verse friction and mills manipulation with intervention of MWD and transverse friction towards consequence pain reduction tennis elbow type II. Methods: 16 person at me-disakti clinic - Sample at as into 2 groups that is 8 person in groups treatment at give therapy mwd, tranverse friction and mills manipulation and 8 person in control groups at give therapy mwd and tranverse friction. Tennis elbow be a disturbance that in group muscle ekstensor wrist especially in ekstensor carpi radialis brevis and longus. While tennis elboe type II be certain disturbance that in area teno periosteal ektensor car-piradialis brevis, where tenoperiosteal ekstensor carpi radialis brevis experience micro-ruptur pulling consequence that over do from muscle ekstensor carpi radialis brevis con-traction. Therapy gift mwd, tranverse friction and mills manipulation in condition tennis elbow type II can demote pain according to have a meaning and give influence differ-rence that have a meaning at compare therapy mwd and transverse friction. Result: This matter is proved in statistics testing that shows value p = 0,035, Intervention mwd, transverse friction and mills manipulation more have a meaning in demote consequence pain tennis elbow type II at compare with therapy mwd and transverse friction.keywords: Tennis Elbow, Manipulation, Intervention